Pengembangan Perangkat Soft Skill Assessment pada Pembelajaran Berbasis Masalah untuk Meningkatkan Keterampilan Kolaborasi, Komunikasi dan Kepedulian Sosial Peserta Didik - Zahra Maria Ulfa; Undang Rosidin (Postgraduate, University of Mataram, 2024)
The research aims to produce the instrument soft skill assessment in problem-based learning that are valid, practical, and effective in assessing students' collaboration, communication, and social skills. This research uses the 4-D development model consisting of four stages: define, design, develop, and disseminate. At the define stage, a preliminary study is carried out in the form of a needs analysis and literature study, then the formulation of objectives. At the design stage, product determination is carried out, product design is created and the instrument soft skills assessment is designed. At the development stage, initial field tests are carried out in the form of expert validation, product revisions, main field tests to obtain data on the practicality and effectiveness of the product, then the final product is obtained. At the disseminate stage, product distribution was carried out on a large scale, but this research only reached the development stage due to limited research time. The research sample consists of tenth-grade students at SMA N 1 Padang Cermin, Lampung. Data collection techniques include methods such as self assessment questionnaires and documentation. Data analysis employs qualitative analysis with descriptive percentage for expert practitioner validation, effectiveness, and quantitative analysis using SPSS for effectiveness. The results of this study indicate that the instrument soft skill assessment in problem-based learning to improve students' collaboration, communication, and social skills in high schools are developed with theoretical, practical, and effective feasibility.